Global water outlook to 2025: averting an impending crisis - Rosegrant, Mark W.; Cai, Ximing; Cline, Sarah A. (International Food Policy Research Institute, 2002)
"... Based on a global model of supply and demand for food and water, this report shows that if current water policies continue, farmers will indeed find it difficult to meet the world’s food needs. Hardest hit will be the world’s poorest people. The results from the model used in this report also show the consequences of changing the course of water policy. Further inattention to water-related investments and policies will produce a severe water crisis, which will lead in turn to a food crisis. A commitment to sustainable use of water, through appropriate policies and investments, however, will lead to a more water- and food-secure world. Water may be a scarce resource, but humans have developed many ways of using it more efficiently — that is, getting more from each unit of water. But water-saving policies, practices, and technologies are of no help if they are not used. Inappropriate incentives and institutions often hinder effective use of water. This report spells out the future results of our current choices." -- Authors' Introduction